PENYALURAN ZAKAT SECARA LANGSUNG KEPADA MUSTAHIK - Muhammad, Muhammad (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2024)
This study aims to determine the distribution of zakat directly to mustahik. The research method used is qualitative method, in obtaining data using library research method, by collecting data through literature. The results of this study show that zakat is a pillar of Islam that has two dimensions, worship and social, the collection, management and distribution of zakat are carried out by official institutions that have been established by the government. The distribution of zakat by unjust rulers is valid, according to the opinion of some scholars. Amil is an officer who takes, manages and distributes zakat to mustahik zakat which has been determined in the text of the Qur'an and hadith.